Comparison of the core training and mobility training effects on basketball athletic performance in young players: a comparative experimental study - Amato, A.; Cortis, C.; Tropea, M.; Politi, M.; Fusco, A.; Musumeci, G. (Sports, 2025)
This study compared the effects of core (CTG) or mobility training (MTG) on basketball-specific skills in youth players, focusing on dynamic balance. Both training modalities have a recognized role in enhancing performance, but few studies have examined their impact on this population. Thirty-one young (age 14.71 ± 2.27 years) males were assigned to an 8-week CTG or MTG. Overhead Squat, Y-Balance Test, Agility T-Test, Sit-and-Reach, Functional Hop Tests, and the Balance Error Scoring System were assessed before (pre) and after (post) the intervention for both dominant (D) and non-dominant (ND) limbs. Both groups improved the postero-lateral direction of the Y-Balance Test for the D (CTG, MD [95% CIs] = -8.108 [-15.620, -0.595], p = 0.035; MTG, MD [95% CIs] = -15.234 [-23.512, -6.956], p = 0.024) and ND (CTG, MD [95% CIs] = -9.110 [-16.150, -2.070], p = 0.013; MTG MD [95% CIs] = -13.899 [-21.657, -6.141], p = 0.001) limb and the medial reach for D (CTG, MD [95% CIs] = -17.279 [-26.364, -8.194], p = 0.001; MTG, MD [95% CIs] = -22.050 [-32.061, -12.039], p = 0.03) and ND (CTG, MD [95% CIs] = -9.309 [-17.093, -1.526], p = 0.021; MTG, MD [95% CIs] = -13.614 [-22.190, -5.037], p = 0.003), the Overhead Squat Test (CTG, MD [95% CIs] = -3.059 [-3.797, -2.321], p = 0.001; MTG, MD [95% CIs] = -3.643 [-4.456, -2.830], p = 0.001), and Agility T-Test (CTG, MD [95% CIs] = 0.572 [0.072, 1.073], p = 0.026; MTG, MD [95% CIs] = 0.696 [0.145, 1.248], p = 0.024) skills. Only CTG showed a significant improvement (MD [95% CIs] = -8.294 [-16.162, -0.426], p = 0.04) in single-leg hop performance for the ND limb. No significant improvements were observed in static balance or flexibility. No time × group effect was found. Both interventions improved key basketball-specific motor abilities and could be added to the basketball training session without adverse effect.